Barriers to Cervical Cancer Screening and Treatment in the Dominican Republic: Perspectives of Focus Group Participants in the Santo Domingo Area. (March 2020) - Liebermann, Erica J.; VanDevanter, Nancy; Shirazian, Taraneh; Frías Gúzman, Natalia; Niles, Mimi; Healton, Cheryl; Ompad, Danielle
Introduction: Cervical cancer is the second leading cause of cancer death among women in the Dominican Republic, and high rates persist despite existing Pap smear screening programs. The purpose of this study was to explore Dominican women's knowledge and attitudes regarding human papillomavirus (HPV) and cervical cancer, cervical cancer screening practices, and perceived barriers and facilitators to early detection of cervical cancer.Method: Six focus groups ( N = 64) were conducted in Spanish in urban, suburban, and rural locations, in private and public school settings, community and workplace settings, in or near Santo Domingo, as part of a larger study on barriers and facilitators to HPV vaccine implementation. Audio recordings were transcribed verbatim and translated from Spanish to English. Qualitative data analysis used inductive and deductive approaches.Results: Knowledge regarding HPV and cervical cancer varied across groups, but all agreed there was significant stigma and fear regarding HPV. Most women reported having Pap screening at least yearly. Follow-up of abnormal Pap testing was less consistent, with cost and uncertainty about provider recommendations identified as barriers.Discussion: Broader examination of provider-level and health system barriers and facilitators to cervical cancer prevention in the Dominican Republic is essential, in order to inform interventions to improve the effectiveness of cervical cancer screening and treatment programs and reduce preventable deaths.